Pemberdayaan Petani Kelapa dalam Mengolah Gula Merah di Desa Besan, Kecamatan Dawan, Kabupaten Klungkung - SITUMORANG, SHINTA RODAME; SUARDI, I DEWA PUTU OKA; PARINING, NYOMAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022DO - 10.24843/JAA.2022.v11.i01.p36, 2022)
Empowerment of Coconut Farmers in Brown Sugar Processing in Besan Village, Dawan District, Klungkung Regency.  Besan Village is a village that has few human resources despite its good natural resource potential. This can be seen from the brown sugar processing business which still uses traditional methods and limited marketing, hence farmers do not get much income from brown sugar production. This study aims to determine the potential of coconut farming and brown sugar processing business and to analyze the empowerment efforts of coconut farmers in the brown sugar processing business in Besan Village, Dawan District, Klungkung Regency. This study uses descriptive qualitative method. Eight informants were selected by using purposive   method, namely the entire population of farmers who are still producing brown sugar. The result of this study indicates that brown sugar processing resources in Besan Village which includes natural resources, human resources, financial resources, and technological resources are sufficient. The efforts to empower brown sugar producer farmers, which include human development, business development, institutional development, and environmental development has been sufficient.